Influence of Waste Marble Dust on the Improvement of Expansive Clay Soils - Hassan A. M. Abdelkader; Mohamed M. A. Hussein; Haiwang Ye (Advances in Civil Engineering)
The marble process industry from Shaq Al-Thouban region, which is located in East Cairo, Egypt, produces a huge amount of marble wastes every day during the cutting and processing stages. Up to now, most of these wastes are dumping on open land which creates serious environmental problems. The amount of waste marble from the processing stage is about 20 to 25% of the total processed stone. Egypt also suffers from the problem of expansive soil that occupies a large area of its lands, especially in the new cities that are built on these lands. The primary purpose of this study is to use this waste material in the soil stabilization in point of view utilization of this waste as local low-cost materials and elimination of their negative environmental impacts. The waste marble dust was mixed with expansive soil samples with various percentages of 5%, 10%, 15%, 20%, and 25% by dry weight of soil. Different tests including Atterberg’s limits, standard Proctor compaction, unconfined compressive strength (UCS), California bearing ratio (CBR), swelling percentage, linear shrinkage (LS) tests, and XRF and XRD analyses were conducted for natural and marble dust stabilized soils. The soil mixtures used for UCS, CBR, and swell tests were compacted at the optimum moisture content (OMC) and maximum dry density (MDD) using the standard Proctor compaction method and cured for 7 days. The results of the tests showed that there are significant effects in enhancing the properties of expansive soils. Also, the results showed that as the percentage of the marble dust increases the plasticity index, the swelling potential of the expansive clayey soil decreases. Furthermore, the optimum moisture content decreases, and the maximum dry density increases. Also, UCS, CBR, and the calcite content of the soil mixtures increase with the increase in marble dust content.